The Psychology Behind Words: Understanding Interpersonal Communication Among Undergraduate Students - Vimala, Govindaraju; Nor Hasniah, Ibrahim (INTERNATIONAL JOURNAL OF RESEARCH AND INNOVATION IN SOCIAL SCIENCE (IJRISS), 2025)
The discourse surrounding education today often highlights technical proficiency, yet academic analysis reveals that interpersonal communication (IPC) is central to the lives of undergraduate students, fundamentally shaping friendships, academic collaboration, and professional development trajectories. Communication is not established as "simply a skill" that everyone can utilize effectively; rather, it is a complex, valuable discipline that necessitates specialized study to achieve true proficiency. An education focused on communication equips individuals with the capacity for scientific research through diverse approaches including rhetorical, qualitative, and quantitative studies alongside domain knowledge in areas like business, political, and interpersonal communication. This article analyzes the relationship between human psychology and interpersonal communication, emphasizing how perceptions, emotions, and cognitive processes affect how students express themselves, settle disputes, and form bonds. The study makes the case that improving interpersonal communication abilities benefits students' social and academic lives as well as their readiness for professional settings where successful human connection is crucial.